2011
DOI: 10.1007/s00468-011-0551-0
|View full text |Cite
|
Sign up to set email alerts
|

Hydraulic redistribution in Eucalyptus kochii subsp. borealis with variable access to fresh groundwater

Abstract: Salinity caused by land clearing is an important cause of land degradation in the Western Australian wheatbelt. Returning a proportion of the cleared land to higher water use perennial vegetation is one option for reducing or slowing the salinisation of land. Over the course of a year patterns of water use by Eucalyptus kochii subsp borealis (C. Gardner) D. Nicolle, a mallee eucalypt species, were monitored in three landscape positions with different water availability. One treatment had groundwater at 2 m, a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 39 publications
0
14
2
Order By: Relevance
“…Brandle et al 2009). It is also within the measured root extent of mallees (Sudmeyer et al 2004) or extent inferred from reduced soil water content (Robinson et al 2006;Brooksbank et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Brandle et al 2009). It is also within the measured root extent of mallees (Sudmeyer et al 2004) or extent inferred from reduced soil water content (Robinson et al 2006;Brooksbank et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…In Africa, hydraulic lift amounted to 20% and 17.5% of the total volume transpired by Vitellaria paradoxa and Parkia biglobosa, respectively, in a semiarid Sahelian Parkland environment (Bayala et al, 2008). In Australia, measurements for Eucalyptus kochii have shown that water redistributed by hydraulic lift contributes up to 27% of daily transpiration (Brooksbank et al, 2011a); planting deep rooting trees that are able to exploit groundwater via hydraulic lift increased water use and biomass production by up to sixfold and tenfold, respectively, because roots were able to reach the relatively shallow water table (Brooksbank et al, 2011a(Brooksbank et al, , 2011b(Brooksbank et al, , 2011c. The dimorphic root system of F. albida has both vertical and lateral roots, which allow it to tap groundwater to substantial depths, while still exploiting the surface horizons where nutrient supplies are greatest, suggesting the existence of hydraulic lift (Roupsard et al, 1999).…”
Section: Importance Of Hydraulic Liftmentioning
confidence: 99%
“…Evidence for young eucalypts or tagasaste fodder hedgerows has shown that their roots remove water from below the crop rooting zone between the tree belts. Furthermore, strategic placement of trees in the landscape minimizes the land area required to be planted to induce the desired effect on local hydrology (Brooksbank et al, 2011a). Eucalyptus is renowned for its high water consumption, competitiveness, fire risk and suppression of biodiversity, and is rarely recommended for AF.…”
Section: Impact Of Trees On Water Balancementioning
confidence: 99%
“…Indeed, to the best of our knowledge, all studies on HR conducted in saline environments (e.g. Armas et al ; Brooksbank et al ; and several of the studies conducted in the Mono Basin ecosystem in California; e.g. Snyder et al ; Aanderud and Richards ) suggest that the redistribution of water occurred from moist saline locations to dry but less saline patches (Table ).…”
Section: Introductionmentioning
confidence: 95%
“…Conversion made assuming that field capacity of the soils was 0.16 m 3 m −3 , and wilting point was 0.05 m 3 m −3 (Brooksbank et al ).…”
Section: Introductionmentioning
confidence: 99%